2020
DOI: 10.1021/acs.langmuir.0c02584
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Induced Morphology Modulation in Spin Coated PS/PMMA Blend Thin Films

Abstract: The influence of adding nanoparticles on the ascast morphology of spin coated immiscible polystyrene/poly­(methyl methacrylate) (PS/PMMA) thin films of different thickness (h E) and composition (R B, volume ratio of PS to PMMA) has been explored in this article. To understand the precise effect of nanoparticle addition, the morphology of PS/PMMA thin blend films spin cast from toluene on a native oxide covered silicon wafer substrate was first investigated. It is seen that in particle free films, the generic m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…It is well-known that a PS-PMMA blend consists of laterally-separated PS-and PMMA-rich phases at ambient conditions. 7,[39][40][41][42][43][44] Herein, using correlative topographical, molecular, and elemental information, we demonstrate that besides the previously-observed lateral phase separation, a vertical phase separation also takes place at the top ca. 20 nm of the PS-PMMA blend surface.…”
Section: Introductionmentioning
confidence: 49%
“…It is well-known that a PS-PMMA blend consists of laterally-separated PS-and PMMA-rich phases at ambient conditions. 7,[39][40][41][42][43][44] Herein, using correlative topographical, molecular, and elemental information, we demonstrate that besides the previously-observed lateral phase separation, a vertical phase separation also takes place at the top ca. 20 nm of the PS-PMMA blend surface.…”
Section: Introductionmentioning
confidence: 49%
“…When thiol-capped AuNP is spin coated along with PS from toluene, it migrates to the free surface during spin coating itself, which has been recently shown by us based on X-ray photoelectron spectroscopy and X-ray scattering …”
Section: Discussionmentioning
confidence: 82%
“…Before we try to explain some of the unique findings on dewetting of NP-containing PS thin films, we would like to highlight certain important and critical issues which are already known and are likely to facilitate subsequent discussion: In TA-mediated dewetting of NP-containing PS films, it has been shown that the particles migrate to the substrate only when the surface energy of the substrate (γ S ) is higher than that of the particles, provided the particles are dispersed in the film When thiol-capped AuNP is spin coated along with PS from toluene, it migrates to the free surface during spin coating itself, which has been recently shown by us based on X-ray photoelectron spectroscopy and X-ray scattering Based on Flory–Huggin’s interaction parameter (χ parameter), it can be seen that the thiol-capped AuNPs are not compatible with both PS and chloroform.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6][7][8][9][10][11] This includes studies on bulk miscible polymer blends, as well as polymer blends nanoconfined in thin films as well as thin films of polymer films with embedded nanoparticles. 12 In general, blending of miscible polymers leads to a distribution of spatial compositions on the nanoscale, which are deviating from that of the bulk averaged concentration. [13][14][15] This does not only influence properties like glassy dynamics, [9][10][11]15,16 glass transition and fragility (see for instance ref.…”
Section: Introductionmentioning
confidence: 99%